UGT1A1 polymorphisms and irinotecan toxicity in colorectal cancer patients - Kim, Tae Won (Henry Stewart Talks, 2009)
Irinotecan activity and safety, Metabolism of Irinotecan, Structure of UGT1A, Role of UGT1A1*28 on irinotecan pharmacogenetics, Role of UGT1A1*6 in Asians, Genotype-based dosing of irinotecan, Other candidates: UGT1A enzyme or transporter
Archived at 2021/02/25